Synthesis of Coumarins from in situ Generated Stabilized Phosphorus Ylides in the Presence of Solid Catalysts in Solvent-free Conditions - Ramazani, Ali; Souldozi, Ali; Marandi, Farzin; Reza Kazemizadeh, Ali (Asian Journal of Chemistry, 2016)
Protonation of the highly reactive 1:1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by phenols (1-hydroxynaphthalene and 2-hydroxynaphthalene) leads to vinyltriphenylphosphonium salts, which undergo aromatic electrophilic substitution reaction with conjugate base to produce corresponding stabilized phosphorus ylides. Iron(II) sulfate powder was found to catalyze conversion of the stabilized phosphorus ylides to coumarins in solvent-free conditions at 90°C in 1 h in high conversations. Microwave also was found to catalyze the same reaction in the presence of iron(II) sulfate powder in solvent-free conditions at microwave power 1 kW in 1 min. Na2SO4, NaHSO4 and CuSO4 powders are not able to catalyze the reaction. ZnSO4 powder is able to catalyze the reaction (only in the cases of 2-hydroxynaphthalene).